2015
DOI: 10.1109/tps.2015.2435160
|View full text |Cite
|
Sign up to set email alerts
|

$W$ -Band Multiple Beam Staggered Double-Vane Traveling Wave Tube With Broad Band and High Output Power

Abstract: A design study for a high-power, high-efficiency, high-growth-rate wideband traveling wave tube (TWT) in W -band using a staggered double-vane slow-wave structure (SWS) combined with three plan alignment pencil beams is described in this paper. The electromagnetic characteristic simulation shows that it has a wide bandwidth, high interaction impedance (about two to three times higher than those of the same structures with the sheet beam scheme), and a more simply designed input/output coupler. 3-D particle-in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Thus, we can calculate the value of synchronous phase velocity and the length of the single period SDV-SWS p by using (1) and (2), where v p is the phase velocity of electrons, c is the speed of light in vacuum. Then, the effects of each structure parameters on dispersion characteristics for SDV-SWS can be studied thoroughly, and the results are similar to our previous work 11 . As l increases, the whole phase velocity decreases; as h increases, the phase velocity of high frequency decreases but that of low frequency keeps the same.…”
Section: Dispersion Characteristicssupporting
confidence: 73%
See 4 more Smart Citations
“…Thus, we can calculate the value of synchronous phase velocity and the length of the single period SDV-SWS p by using (1) and (2), where v p is the phase velocity of electrons, c is the speed of light in vacuum. Then, the effects of each structure parameters on dispersion characteristics for SDV-SWS can be studied thoroughly, and the results are similar to our previous work 11 . As l increases, the whole phase velocity decreases; as h increases, the phase velocity of high frequency decreases but that of low frequency keeps the same.…”
Section: Dispersion Characteristicssupporting
confidence: 73%
“…In this paper, to further improve the bandwidth, keep the high output power and avoid the serious problems of sheet beam formation and long distance transportation, instead of using the only fundamental single mode to match with the electron beam, the fundamental double-mode SDV-SWS with planar alignment three-pencil beam in W-band is studied thoroughly. It is found that the beam-wave matching band indeed increases as twice compared to our previous work 11 . Also, the interaction impedance is also about two times higher than that of sheet beam SWS in the same band.…”
supporting
confidence: 40%
See 3 more Smart Citations